Nilai Satya dan Pengendalian Internal Sebagai Strategi Meminimalkan Tindakan Fraud Pada LPD di Kabupaten Buleleng - Pasek, Gede Widiadnyana; Trisnawati, Ni Luh De Erik (Universitas Pendidikan Ganesha, 2021)
This study aims to find empirical evidence regarding the effect of Satya Value, and Internal Control on the tendency of accounting fraud at the Village Credit Institution of Buleleng Regency. This research is located at the Village Credit Institution (LPD) of Buleleng Regency. This study uses a quantitative approach. The research sample used in this research is 266 respondents. Hypothesis testing in this study uses multiple regression analysis techniques with a statistical approach which is operated through the SPSS program. The results of this study indicate that the value of Satya and Internal Control has an effect on the tendency of accounting fraud.